'dass diese tauben Geschichten aufflattern': Narrative, Translingual Creativity and Belonging in Katja Petrowskaja's Vielleicht Esther (2014). Issue 1 (4th June 2020) - Weiss-Sussex, Godela
This article argues that reading Katja Petrowskaja's Vielleicht Esther in the context of minor literature as a literature of deterritorialisation highlights its sense of liberation and emphasises the creation of associations – aspects that are crucial to this transnational and translingual book about retrieving memory across space and time. Going beyond the idea of a binary relationship between minor and major literature and instead focusing on rhizomatic affiliation emerges as key. A wider framework of analysis is also provided by ideas that derive from or have been developed in conjunction with Deleuze and Guattari's thinking: the idea of minor transnationalism (Françoise Lionnet, Shu-Mei Shih), the concepts of multi- and translingualism (Leslie Adelson, Steven G. Kellman) and the ethics of relationality (Sara Ahmed ) and multidirectionality in postmemory discourses (Hirsch, Rothberg). Combined, these ideas prove to be useful tools for understanding Petrowskaja's handling of narrative, language and belonging in Vielleicht Esther . Tweetable Abstract: Reading Petrowskaja's Vielleicht Esther as literature of deterritorialisation throws light on her handling of narrative, language and belonging.